Trend 2000 - 2003. Statistics Canada. CANSIM: Culture and Leisure - Government Spending on Culture | Country: Canada | Province: Northwest Territories | Table: Federal government expenditures on culture, by culture activity | Variable: Arts education, Federal government capital expenditures | Units: $CAD x 1,000, 2000-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-047. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Culture and Leisure - Government Spending on Culture | Country: Canada | Province: Northwest Territories | Table: Federal government expenditures on culture, by culture activity | Variable: Arts education, Federal government capital expenditures | Units: $CAD x 1,000, 2000-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-047. Dataset: Provides statistics on funding of culture programs and institutions by all levels of government in Canada, including libraries, heritage activities, performing arts, literary arts, visual arts and crafts, broadcasting, film, and video. Government spending on culture by province/territory and by type of expenditure (operating and capital expenditures as well as operating and capital grants and contributions) is also included. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Government and Politics, Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Performing Arts, Leisure Activities, Culture, Libraries, Government Spending